Understanding the macroeconomic effects of public research: An application of a regression-microfounded CGE-model to the case of the Fraunhofer-Gesellschaft in Germany - Allan Grant; Gioele Figus; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
Estimating the economic returns to public science investments has been a key topic in economics. However, while in particular microeconomic approaches have been proposed, only a few studies have tried estimating the macroeconomic effects of public science investments. In this paper, we propose a micro-rooted macro-modelling framework, which combines the strength of an econo-metric causal identification of key effects with the power of a Computable General Equilibrium (CGE) framework, and provides additional economic structure of the estimates allowing us a fine-grained sectoral differentiation of all effects. Applying our approach to the German Fraunhofer-Gesellschaft, the world's largest publicly funded organization for applied research, we show that macroeconomic returns are - irrespective of econometric specification - a high multitude of the original investment costs. In specific, the activities by the Fraunhofer-Gesellschaft increase German GDP by 1.6% and employment by 437,000 jobs. Our CGE analysis further shows that the effects concentrate in chem-icals, pharmaceuticals, motor vehicles and machinery sectors. The substantial size of our estimated effects corroborate recent macroeconomic evidence on the social returns to innovation.
urn:nbn:de:0011-n-6483707
Keywords: 330; macroeconomic Effects of public Research; Fraunhofer-Gesellschaft; Regression-microfounded CGE-model